Pengaruh Bimbingan Kelompok Dengan Teknik Self Talk Untuk Meningkatkan Kesadaran Diri (Self Awareness) pada Siswa Kelas VIII Tingkat SMP - Mayora, Refa; Syafriafdi, Non; Umari, Tri (CV. Rayyan Dwi Bharata, 2025)
This research aims to determine whether group counseling services using the self-talk technique have an effect on improving self-awareness in class VIII of Junior High School Level. This research is a quantitative study using an experimental method with a one-group pretest-posttest design involving a single subject group. Data collection was carried out through the distribution of a self-awareness scale, which was then analyzed using the Wilcoxon test with the help of SPSS Version 25. The results of this study indicate that there is a difference in the level of self-awareness of students before and after receiving group counseling services with the self-talk technique. Furthermore, the study found that the contribution of group counseling services with the self-talk technique to students' self-awareness was 49%, while the remaining 51% was influenced by other factors such as family support, social interactions, education, and cultural values.